If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3n + -3 = -9 Reorder the terms: -3 + 3n = -9 Solving -3 + 3n = -9 Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '3' to each side of the equation. -3 + 3 + 3n = -9 + 3 Combine like terms: -3 + 3 = 0 0 + 3n = -9 + 3 3n = -9 + 3 Combine like terms: -9 + 3 = -6 3n = -6 Divide each side by '3'. n = -2 Simplifying n = -2
| 14x+5=105 | | 160000+5x=200000 | | 3x-(-2+4x)x=5 | | 2+2v=10 | | Y=27.5+-2.5x | | 6.2=x/4 | | 5x+2x=4x | | 30-15y+2y=10 | | x/1.5*1.5 | | 3+16y=11 | | 8/9x2/3 | | .25y+.10x=2.75 | | 5/8-11/14 | | 200-5x=160 | | 8x+3(x-5)+8=-18 | | 4b+7=3 | | 3x-(2-4x)x=5 | | m+36=5m | | 18.3+x= | | .10x+.25y=2.75 | | 3x-(-2-4x)x=5 | | 7(3x+2)=77 | | -2y(y+6)=y+3+2y | | -3.2+14z=15z | | 24=y/6 | | -3x+(2+4x)x=5 | | 8p-7=0 | | .4y-8=.4y+16 | | 8.1s-9=7.1s-9 | | 1-(-7)=-6 | | 3x+(2+4x)x=5 | | 12-4n=2 |